Does the frequency of molecular monitoring after tyrosine kinase inhibitor discontinuation affect outcomes of patients with chronic myeloid leukemia?. Issue 13 (27th February 2017) - Kong, Jee Hyun; Winton, Elliott F.; Heffner, Leonard T.; Chen, Zhengjia; Langston, Amelia A.; Hill, Brittany; Arellano, Martha; El‐Rassi, Fuad; Kim, Audrey; Jillella, Anand; Kota, Vamsi K.; Bodó, Imre; et al.
Abstract : BACKGROUND: To the authors' knowledge, the optimal frequency of monitoring after tyrosine kinase inhibitor (TKI) discontinuation in patients with chronic myeloid leukemia (CML) has not been established. Data regarding the discontinuation of second‐generation TKIs used in first‐line treatment or after the failure of first‐line treatment with TKIs are limited. Herein, the authors report real‐world experience with "reduced frequency" molecular monitoring in patients with CML in all phases who discontinued treatment with imatinib, dasatinib, or bosutinib. METHODS: The records of patients who discontinued TKIs were reviewed. Patients who discontinued TKIs were monitored prospectively on an intended schedule of monthly blood quantitative reverse transcriptase‐polymerase chain reaction for BCR‐ABL1 for 3 months, quarterly for 12 months, and every 6 months thereafter until loss of major molecular response (MMR). After loss of MMR, the TKI that previously was discontinued was reinitiated. RESULTS: Between January 2010 and September 2015, a total of 24 patients in chronic (21 patients), accelerated (2 patients), and lymphoid blast (1 patient) phase discontinued imatinib (16 patients), dasatinib (5 patients), or bosutinib (3 patients) used in the front‐line treatment or beyond. Blood quantitative reverse transcriptase‐polymerase chain reaction for BCR‐ABL1 was performed 1.3 ± 0.7 times within the first 3 months (24 patients) and 2.7 ± 1.4 times in the following 12 months (18 patients). With a median follow‐up of 36.5 months (range, 3.2‐67.4 months), the probabilities of treatment‐free remission at 1 year and 2 years were 65.7% (95% confidence interval, 55.8%‐75.6%) and 59.7% (95% confidence interval, 49.1%‐70.3%), respectively. Loss of MMR was observed in 9 patients at a median of 2.8 months (range, 1.8‐14.2 months) after discontinuation of TKIs. CONCLUSIONS: With the limitations of a small sample size, the results of the current study demonstrate that less frequent monitoring of BCR‐ABL1 does not appear to affect outcomes, and that discontinuation of TKIs used as first‐line treatment or beyond after resistance or intolerance to first‐line treatment appears feasible. Cancer 2017;123:2482–88. © 2017 American Cancer Society . Abstract : Less frequent monitoring of BCR‐ABL1 after discontinuation of tyrosine kinase inhibitors in patients with chronic myeloid leukemia does not appear to affect outcomes. The discontinuation of tyrosine kinase inhibitors used as first‐line treatment or beyond after resistance or intolerance to first‐line treatment appears to be feasible.